Autophagy modulation in breast cancer utilizing nanomaterials and nanoparticles - Gharoonpour, Azar; Simiyari, Dorsa; Yousefzadeh, Ali; Badragheh, Fatemeh; Rahmati, Marveh (Frontiers in Oncology, 2023)
Autophagy regenerates cellular nutrients, recycles metabolites, and maintains hemostasis through multistep signaling pathways, in conjunction with lysosomal degradation mechanisms. In tumor cells, autophagy has been shown to play a dual role as both tumor suppressor and tumor promoter, leading to the discovery of new therapeutic strategies for cancer. Therefore, regulation of autophagy is essential during cancer progression. In this regard, the use of nanoparticles (NPs) is a promising technique in the clinic to modulate autophagy pathways. Here, we summarize the importance of breast cancer worldwide, its classification, current treatment strategies, and the strengths and weaknesses of available treatments are discussed. We also describe the application of NPs and nanocarriers (NCs) in breast cancer treatment and their capability to modulate autophagy. We then discuss the advantages and disadvantages of NPs in cancer therapy, along with their future applications. The purpose of this review is to provide researchers with up-to-date information on NPs used in breast cancer treatment and their impacts on autophagy pathways.